Zakat Produktif: Tinjauan Literatur dan Implikasinya Terhadap Pembangunan Ekonomi di Indonesia: Productive Zakat: Literature Review and Implications for Economic Development in Indonesia - Fahmi Fauzi; Nasution, Yenni Samri Juliati (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
Productive zakat is an innovative approach to zakat management that focuses on the economic empowerment of mustahik (zakat recipients) to increase income in a sustainable manner. This research aims to explore the role of productive zakat in the context of economic development in Indonesia, by referring to data from the National Zakat Amil Agency (BAZNAS) and various literature sources. The method used in this research is a literature review study, which involves collecting and analyzing various relevant literature sources. The findings show that productive zakat not only increases mustahik income, but also creates jobs, improves skills, and encourages social solidarity in society. By providing access to capital and training, productive zakat helps mustahik transform into muzakki (zakat givers), creating a positive cycle of sustainability. However, to maximize the potential of productive zakat, government policies are needed that support transparency, increase public awareness, collaboration with the private sector, and effective monitoring and evaluation. This research is expected to provide deeper insight into strategies for optimizing the productive role of zakat in national economic development.